Forensic Identification of Human Blood: comparison of two one-step presumptive tests for blood screening of crime scene samples. - Andrade, Ana Flávia Belchior; Siqueira, Maria Emília Cambria Guimaro; Arantes, Luciano Chaves; Queiroz, Larissa Silva; Silva, Rayane Luiza Viegas; Ramalho, Eduardo Dias (Revista Brasileira de Criminalística, 2014)
Blood is the most common body fluid found at crime scenes. One-step presumptive tests have been designed as a rapid immunological test for the qualitative detection of human hemoglobin in stool samples (faecal occult blood) their usefulness for forensic purposes has been demonstrated before. In this study we compare Hexagon OBTI kit and FOB One-step Bioeasy kit sensitivity in the analysis of diluted blood samples. With Hexagon OBTI, positive test results are achieved in whole blood dilutions up to 1:1.000. Sensitivity decreased with aged samples, if samples were not stored under low temperatures regardless of which presumptive test is used. Whole blood tests must take into consideration that “hook” effect may interfere. Comparing both tests, OBTI Hexagon Kit is more sensible to detect diluted blood, showing a wider detection window in all conditions. This is interesting when analyzing forensic samples as forensic analysts usually do not know about the history of the analyzed sample before its collection.